Traditional management of Cactaceae by local populations in the semi-arid region of Brazil - Pedrosa, Kamila Marques; Lopes, Sérgio de Faria; Carvalho, Thamires Kelly Nunes; Lucena, Camilla Marques de; Lima-Nascimento, Ailza Maria de; Lucena, Reinaldo Farias Paiva de (Ethnobiology and Conservation, 2020)
Cactaceae species are important resources in the semi-arid region of Brazil and have been used and managed in a specific way by farmers to optimize and ensure the availability of cacti to rural communities. Thus, this study aimed to investigate management techniques used by residents of four rural communities in the municipality of Cabaceiras, Paraíba, Northeast Brazil. For this, semi-structured interviews were conducted with 44 informants. Seventeen of them reported performing some type of management using the following cacti species: Pilosocereus gounellei (F.A.C. Weber) Byles & G.D. Rowley subsp. gounellei, Cereus jamacaru DC. subsp. Jamacaru, Pilosocereus pachycladus F. Ritter subsp. pernambucoensis (F. Ritter) Zappi, Tacinga palmadora (Britton & Rose) N.P. Taylor & Stuppy, and Melocactus zehntneri (Britton & Rose) Luetzelb. Ex situ and in situ management techniques were recorded. The first one performed by transplantation of propagules and the second one by tolerance. The species propagation is carried out using shoots and vegetative parts. Of the species identified, only Cereus jamacaru has more than one form of management. In addition to management, informants use rudimentary techniques such as burning the vegetative parts for fodder purposes.